The War Game - Watkins, Peter (United Kingdom, 1965)
Originally made for British television, this semi-documentary directed by Peter Watkins was never aired on television because it was considered too shocking and horribly realistic; instead after a delay it was released theatrically and won the Academy Award as best feature documentary of 1966. This film shows what could happen in Great Britain if it were under nuclear attack and the after-effects its survivors would suffer in a post-nuclear-war world.